Strategic Management in Private Universities Based on Risk Analysis and Balanced Scorecard at De La Salle Catholic University Manado - Koleangan, Christoforus Adri Pieter (International Journal of Information Technology and Education, 2024)
The dynamics of change cannot be avoided by any organization anywhere, including universities throughout Indonesia, of which De La Salle Manado Catholic University, abbreviated as UKDLSM, is a part. This research aims to: Know and describe the extent of UKDLSM strategic management, Know and describe the UKDLSM risk register, and Develop a strategic management model based on risk analysis and a balanced scorecard that can be implemented by universities. This research method is a case study. The research was carried out in 3 stages consisting of the research results stage on the three research problems, namely UKDLSM strategic management, risk analysis on UKDLSM, and UKDLSM strategic management based on risk analysis and balanced scorecard, then from the research results continued to the second stage, findings from the research results and then The third stage is a discussion of the research results and findings. The results of this research show that the management strategy used by De La Salle Catholic University Manado is a conventional model using conventional tools, namely SWOT (and assisted by IFE and EFE matrix analysis. The results of this research also show that it has not been implemented completely to the lowest level and every community member of UKDLSM academics. This research concludes that in formulating the strategic plan, the drafting team has not studied the complexity of the internal environment, the external environment, and the nature of the problems faced by UKDLSM.